A high-foaming two-component polyurethane adhesive and preparation method thereof
By optimizing the formulation and composition, a high foaming two-component polyurethane adhesive was developed, which solved the problem that the existing technology could not meet the needs of color steel plate and rock wool composite applications, achieved high foaming rate and good bonding performance, and improved the strength and processing efficiency of the composite structure.
Patent Information
- Application Number
- CN202510019923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing polyurethane foam glue cannot meet the composite application requirements between color steel plates and rock wool, especially while maintaining foaming rate and bonding performance, it is difficult to meet the composite requirements of sandwich sandwich structures.
By optimizing the formulation system, high-foaming two-component polyurethane adhesive, including foaming main agent and curing agent, using a combination of castor oil, elastomer polyether polyol and glycerin, and combining water as a foaming agent, the mass ratio of inorganic fillers and the compounding of catalysts is controlled to ensure that the foaming rate, hardness and bonding performance of the product reach the required level.
A polyurethane adhesive with a high foaming rate (600-900%) is achieved, ensuring good bonding between color steel plates and rock wool, avoiding hole collapse problems, and achieving the required strength in a short time, improving processing efficiency.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane adhesives, in particular to a high-foaming two-component polyurethane adhesive and a preparation method thereof. Background Art
[0002] Polyurethane adhesive refers to a polymer containing carbamate groups ( ) adhesive, which has many excellent properties such as high reactivity, strong bonding force, room temperature curing, and impact resistance, and is therefore widely used in various fields. A Chinese patent (authorization announcement number CN114045147B) discloses a one-component polyurethane foam adhesive and its preparation method and application, which uses a mixed polyol of vegetable oil polyol, polyester polyol and polyether polyol in combination with other raw materials in its formula system, so that the provided adhesive meets the requirements of waterproof performance and bonding performance of foamed ceramic tiles. A Chinese patent (authorization announcement number CN111234763B) discloses a composite foam adhesive for lightweight particleboard, which is mainly designed for lightweight particleboard. Specifically, the isocyanate group (-NCO) in the foamed polyurethane reacts with modified azodicarbonamide to form foam, fill the gap between the wood chips, and firmly combine the wood chips together, so that good contact can be formed between the wood chips-adhesive-wood chips, thereby obtaining a lightweight particleboard. However, different application fields have different performance requirements for polyurethane adhesives, and the research and development of foam adhesives is in its infancy. Existing polyurethane foam adhesives cannot meet the composite application requirements between color steel plates and rock wool. Summary of the invention
[0003] In order to solve the above problems, the present invention provides a high-foaming two-component polyurethane adhesive, which meets the composite application requirements of the sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth) by optimizing the product formula system.
[0004] On one hand, the present invention provides a high-foaming two-component polyurethane adhesive, comprising a foaming main agent and a curing agent. The raw materials for preparing the foaming main agent include at least 10-20 parts of castor oil, 30-40 parts of elastomer polyether polyol, 45-65 parts of inorganic filler, 0.1-0.3 parts of catalyst, 0.1-1 parts of foam leveling agent, 0.01-0.2 parts of defoaming agent and 0.5-0.8 parts of water, by weight.
[0005] As a preferred technical solution, the mass ratio of castor oil to elastomeric polyether polyol is (10-20):(25-40), preferably (10-15):(25-35).
[0006] As a preferred technical solution, the elastomeric polyether polyol has a hydroxyl value of 200-400 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C.
[0007] Preferably, the elastomeric polyether polyol is selected from at least one of DMN500, DMN550 and DMN700, preferably DMN500 (hydroxyl value of 335±10 mgKOH / g, viscosity of 260-380 mPa·s at 25°C), which is sourced from Zibo Dexin Federal Chemical Industry Co., Ltd.
[0008] As a preferred technical solution, the raw materials for preparing the foaming main agent also include 0.1-1 parts by weight of glycerol.
[0009] As a preferred technical solution, the inorganic filler at least includes fumed silica and calcium carbonate.
[0010] Preferably, the mass ratio of the fumed silica to calcium carbonate is (0.3-0.6):(50-60).
[0011] Preferably, the fumed silica is hydrophilic fumed silica, and the specific surface area (BET) of the hydrophilic fumed silica is 175 - 225 m² / g.
[0012] As a preferred technical solution, the catalyst at least includes dibutyltin dilaurate and triethylenediamine.
[0013] Preferably, the mass ratio of dibutyltin dilaurate to triethylenediamine is (2-4):1.
[0014] The polyurethane adhesive provided by the present invention is comprehensively optimized for the composite between color steel plate and rock wool. The color steel plate is a plane, and the core layer rock wool is a porous structure. When the polyurethane adhesive is composited in the sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth), it is necessary to balance the foaming rate, the hardness of the foamed body and the bonding performance. The present invention has found in a large number of exploratory experiments that by controlling the addition amount of castor oil and elastomer polyether polyol in the system, and coordinating the introduction of glycerol, the hardness and flat tensile strength of the foamed body are guaranteed without affecting the foaming rate and the rising time of the product, and the bonding and composite requirements of the sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth) are met. In particular, by using an elastomeric polyether polyol with a hydroxyl value of 200-400 mgKOH / g and a viscosity of 200-400 mPa·s at 25°C, in combination with other raw materials in the system, the provided polyurethane adhesive can reach the required strength in a shorter time, thereby avoiding the actual processing efficiency being affected due to the long time it takes to reach the strength, and meeting actual use needs.
[0015] Furthermore, by using water as a foaming agent and controlling the amount of water added in the system, the provided polyurethane adhesive has a foaming rate of 600-900%, which effectively solves the problem of pore collapse of the polyurethane adhesive under high foaming rates. The high foaming rate polyurethane adhesive is filled into the porous structure of the rock wool during the foaming process, fully ensuring the composite strength.
[0016] Furthermore, the two-component polyurethane adhesive provided by the present invention is usually sprayed to compound the color steel plate and the rock wool, and the foaming main agent and the curing agent are mixed in the spiral tube of the spray gun. Therefore, it is necessary to comprehensively control the viscosity and the rising time of the product. During the exploration process, the present invention found that based on the polyol mixture system composed of castor oil, elastomer polyol and glycerol in the present invention, by adopting a catalyst system of dibutyltin dilaurate and triethylenediamine in a ratio of (2-4): 1, the product's starting time is controlled within 20-40s, which greatly increases the operability of the product and avoids the problem of spray gun clogging due to too short starting time and the glue not drying due to too long starting time.
[0017] In addition, the present invention adopts an inorganic filler containing hydrophilic fumed silica, and in particular controls the mass ratio of fumed silica to calcium carbonate in the inorganic filler to (0.3-0.6): (50-60), so that the viscosity of the provided product meets the requirements of spraying application while ensuring the stability of the foaming main agent during storage.
[0018] As a preferred technical solution, the defoaming agent is SX08 defoaming agent (Sixin Technology).
[0019] As a preferred technical solution, the foam leveling agent is Maihao Y-16612.
[0020] As a preferred technical solution, the curing agent is polymeric MDI, preferably Wanhua PM200.
[0021] As a preferred technical solution, the mass ratio of the main foaming agent to the curing agent is 100:(30-50), preferably 100:40.
[0022] Another aspect of the present invention provides a method for preparing a high-foaming two-component polyurethane adhesive, comprising at least the following steps:
[0023] S1. Mixing elastomer polyether polyol, castor oil and glycerin by weight to obtain a polyol mixture;
[0024] S2, adding an inorganic filler to the polyol mixture and stirring and mixing to obtain a mixture;
[0025] S3, add catalyst, foam leveling agent, defoamer and water to the mixture, stir and mix, cool to below 50°C, and discharge to obtain the foaming main agent;
[0026] S4. When using, stir and mix the foaming main agent and curing agent.
[0027] As a preferred technical solution, the stirring and mixing speed in step S1 is 800-1200 r / min, and the stirring and mixing time is 10-20 min.
[0028] As a preferred technical solution, the stirring and mixing speed in step S2 is 1000-2000 r / min, and the stirring and mixing time is 60-80 min (high-speed dispersion will generate heat, and the colloid temperature can reach 70-80° C.).
[0029] As a preferred technical solution, the stirring and mixing speed in step S3 is 1000-2000 r / min, and the stirring and mixing time is 20-40 min.
[0030] Beneficial Effects
[0031] 1. The present invention provides a high-foaming two-component polyurethane adhesive, which meets the composite application requirements of the sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth) by optimizing the product formula system.
[0032] 2. The present invention controls the addition amount of castor oil and elastomer polyether polyol in the system and introduces glycerol to ensure the hardness and tensile strength of the foam without affecting the foaming rate and rising time of the product, thereby meeting the bonding and composite requirements of the sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth).
[0033] 3. The present invention adopts water as a foaming agent and controls the amount of water added in the system to provide a polyurethane adhesive with a foaming rate of 600-900%, which effectively solves the problem of pore collapse of the polyurethane adhesive under high foaming rates. The polyurethane adhesive with a high foaming rate is filled into the porous structure of the rock wool during the foaming process, fully ensuring the composite strength.
[0034] 4. Based on the polyol mixture system composed of castor oil, elastomer polyol and glycerol in the present invention, by adopting a catalyst system prepared by compounding dibutyltin dilaurate and triethylenediamine in a ratio of (2-4): 1, the product's initiation time is controlled within 20-40s, which greatly increases the operability of the product and avoids the problem of spray gun clogging due to too short initiation time and the problem of glue not drying due to too long initiation time.
[0035] 5. The present invention adopts an inorganic filler containing hydrophilic fumed silica, and in particular controls the mass ratio of fumed silica to calcium carbonate in the inorganic filler to (0.3-0.6): (50-60), so that the viscosity of the provided product meets the requirements of spraying applications while ensuring the stability of the foaming main agent during storage. DETAILED DESCRIPTION
[0036] Example 1
[0037] Embodiment 1 of the present invention provides a high-foaming two-component polyurethane adhesive, including a foaming main agent and a curing agent. The raw materials for preparing the foaming main agent include, by weight, 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55.5 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of uniform foaming agent, 0.08 parts of defoaming agent, and 0.7 parts of water.
[0038] The elastomeric polyether polyol is DMN500 (hydroxyl value is 335±10 mgKOH / g, viscosity is 260-380 mPa·s at 25°C), which is sourced from Zibo Dexin Federal Chemical Industry Co., Ltd.
[0039] The inorganic filler is a combination of fumed silica and calcium carbonate.
[0040] The mass ratio of the fumed silica to calcium carbonate is 0.5:55.
[0041] The fumed silica is hydrophilic fumed silica, and the specific surface area (BET) of the hydrophilic fumed silica is 175 - 225 m² / g (AEROSIL 200).
[0042] The model of the calcium carbonate is QT-7692, which comes from Zhejiang Qintang Calcium Industry Co., Ltd.
[0043] The catalyst is a combination of dibutyltin dilaurate and triethylenediamine.
[0044] The mass ratio of dibutyltin dilaurate to triethylenediamine is 3:1.
[0045] The defoamer is SX08 defoamer (Sixin Technology).
[0046] The foam leveling agent is Maihao Y-16612.
[0047] The curing agent is polymeric MDI (Wanhua PM200).
[0048] The mass ratio of the foaming main agent to the curing agent is 100:40.
[0049] Embodiment 1 of the present invention provides a method for preparing a high-foaming two-component polyurethane adhesive, comprising the following steps:
[0050] S1. Mixing elastomer polyether polyol, castor oil and glycerin by weight to obtain a polyol mixture;
[0051] S2, adding an inorganic filler to the polyol mixture and stirring and mixing to obtain a mixture;
[0052] S3, add catalyst, foam leveling agent, defoamer and water to the mixture, stir and mix, cool to below 50°C, and discharge to obtain the foaming main agent;
[0053] S4. When using, stir and mix the foaming main agent and curing agent.
[0054] The stirring and mixing speed in step S1 is 1000 r / min, and the stirring and mixing time is 15 min.
[0055] The stirring and mixing speed in step S2 is 1500 r / min, and the stirring and mixing time is 60 min.
[0056] The stirring and mixing speed in step S3 is 1500 r / min, and the stirring and mixing time is 30 min.
[0057] Example 2
[0058] Example 2 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the raw materials for preparing the foaming main agent include 10 parts of castor oil, 40 parts of elastomeric polyether polyol, 0.1 parts of glycerol, 45 parts of inorganic filler, 0.1 parts of catalyst, 0.3 parts of foaming agent, 0.2 parts of defoaming agent, and 0.5 parts of water.
[0059] Example 3
[0060] Example 3 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that the raw materials for preparing the foaming main agent include 20 parts of castor oil, 30 parts of elastomeric polyether polyol, 1 part of glycerol, 65 parts of inorganic filler, 0.3 parts of catalyst, 0.1 parts of foaming agent, 0.01 parts of defoaming agent, and 0.8 parts of water.
[0061] Comparative Example 1
[0062] Comparative Example 1 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55.5 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of uniform foaming agent, 0.08 parts of defoaming agent, and 0.4 parts of water.
[0063] Comparative Example 2
[0064] Comparative Example 2 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55.5 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of uniform foaming agent, 0.08 parts of defoaming agent, and 1 part of water.
[0065] Comparative Example 3
[0066] Comparative Example 3 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 22.2 parts of castor oil, 21.6 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55.5 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of uniform foaming agent, 0.08 parts of defoaming agent, and 0.7 parts of water.
[0067] Comparative Example 4
[0068] Comparative Example 4 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof, and its specific implementation manner is the same as that of Example 1, except that the catalyst is replaced by dibutyltin dilaurate.
[0069] Comparative Example 5
[0070] Comparative Example 5 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof, and its specific implementation manner is the same as that of Example 1, except that the catalyst is replaced by triethylenediamine.
[0071] Comparative Example 6
[0072] Comparative Example 6 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof, and its specific implementation manner is the same as that of Example 1, except that the mass ratio of dibutyltin dilaurate to triethylenediamine is 1:1.
[0073] Comparative Example 7
[0074] Comparative Example 7 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 55.5 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of uniform foaming agent, 0.08 parts of defoaming agent, and 0.7 parts of water.
[0075] Comparative Example 8
[0076] Comparative Example 8 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of foam leveling agent, 0.08 parts of defoaming agent, and 0.7 parts of water; the inorganic filler is calcium carbonate.
[0077] Comparative Example 9
[0078] Comparative Example 9 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55.8 parts of inorganic filler, 0.25 parts of catalyst, 0.25 parts of foam leveling agent, 0.08 parts of defoaming agent, and 0.7 parts of water; the mass ratio of the fumed silica to calcium carbonate is 0.8:55.
[0079] Comparative Example 10
[0080] Comparative Example 10 of the present invention provides a high-foaming two-component polyurethane adhesive and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the foaming main agent include 13.8 parts of castor oil, 30 parts of elastomeric polyether polyol, 0.33 parts of glycerol, 55.5 parts of inorganic filler, 0.4 parts of catalyst, 0.25 parts of uniform foaming agent, 0.08 parts of defoaming agent, and 0.7 parts of water.
[0081] Performance Testing
[0082] 1. Rising time: After the foaming agent and curing agent in the examples and comparative examples are uniformly mixed (time is 10 seconds), start timing until the colloid starts to foam, stop timing, and record this time as the rising time. The results are shown in Table 1.
[0083] 2. Foaming rate: Mix the foaming agent and curing agent in the embodiment and comparative example evenly (time is 10s) and then spray them on the surface of the color steel plate (the amount of glue applied is 220g / m 2) and then hot-pressed at 45°C for 5 min to prepare a sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth). The volume of the foamed body before and after foaming was tested, and the foaming rate was calculated according to the formula (foaming rate = (final foamed body volume-volume before foaming) / volume before foaming*100%). The results are shown in Table 1.
[0084] 3. According to the national standard GB / T1452 / 2018, the products provided in the embodiments and comparative examples were cured for 1 day to test the tensile strength of the three-layer structure (color steel plate-rock wool-color steel plate) (the amount of glue applied was 220g / m 2 ), the test results are shown in Table 1.
[0085] 4. Mix the foaming agent and curing agent in the embodiment and comparative example evenly (time is 10s) and then spray them onto the surface of the color steel plate (the amount of glue applied is 220g / m 2 ) and then hot-pressed at 45°C for 5 min to prepare a sandwich structure of color steel plate (cement fiber cloth)-rock wool-color steel plate (cement fiber cloth). The hardness of the foam was tested with a hardness tester. The test results are shown in Table 1.
[0086] 5. Viscosity: After the foaming agent and the curing agent in the embodiments and comparative examples were uniformly mixed (time for 10 seconds), a viscometer was used for testing (BROOKFIELD DV2TRVTJ0, No. 5 rotor, 10 rpm, 25° C.). The test results are shown in Table 1.
[0087] Table 1
[0088]
Claims
1. A high foaming two-component polyurethane adhesive, characterized in that: The invention comprises a foaming main agent and a curing agent. The raw materials for preparing the foaming main agent include at least 10-20 parts of castor oil, 30-40 parts of elastomer polyether polyol, 45-65 parts of inorganic filler, 0.1-0.3 parts of catalyst, 0.1-1 parts of foam leveling agent, 0.01-0.2 parts of defoamer, 0.5-0.8 parts of water and 0.1-1 parts of glycerol. The mass ratio of the castor oil and the elastomer polyether polyol is (10-15): (25-35). The hydroxyl value of the elastomer polyether polyol is 335±10 mgKOH / g, and a viscosity of 260-380 mPa·s at 25°C; the inorganic filler comprises at least fumed silica and calcium carbonate; the mass ratio of the fumed silica to calcium carbonate is (0.3-0.6):(50-60), the fumed silica is hydrophilic fumed silica, and the specific surface area of the hydrophilic fumed silica is 175 - 225 m² / g; the catalyst comprises at least dibutyltin dilaurate and triethylenediamine; the mass ratio of the dibutyltin dilaurate to triethylenediamine is (2-4):
1.
2. The high foaming two-component polyurethane adhesive according to claim 1, characterized in that: The mass ratio of the foaming main agent to the curing agent is 100:(30-50).
3. A method for preparing a high-foaming two-component polyurethane adhesive according to any one of claims 1 to 2, characterized in that: At least the following steps are included: S1. Mixing elastomer polyether polyol, castor oil and glycerin by weight to obtain a polyol mixture; S2, adding an inorganic filler to the polyol mixture and stirring and mixing to obtain a mixture; S3, add catalyst, foam leveling agent, defoamer and water to the mixture, stir and mix, cool to below 50°C, and discharge to obtain the foaming main agent; S4. When using, stir and mix the foaming main agent and curing agent.
4. The method for preparing the high-foaming two-component polyurethane adhesive according to claim 3, characterized in that: The stirring and mixing speed in step S1 is 800-1200 r / min, and the stirring and mixing time is 10-20 min.
5. The method for preparing the high-foaming two-component polyurethane adhesive according to claim 3, characterized in that: The stirring and mixing speed in step S2 is 1000-2000 r / min, and the stirring and mixing time is 60-80 min.
6. The method for preparing the high-foaming two-component polyurethane adhesive according to claim 3, characterized in that: The stirring and mixing speed in step S3 is 1000-2000 r / min, and the stirring and mixing time is 20-40 min.
Citation Information
Patent Citations
A compound foaming adhesive for lightweight particleboard
CN111234763B
A one-component polyurethane foam adhesive, its preparation method and application
CN114045147B
Solvent-free two-component foaming polyurethane adhesive and application thereof
CN114276774A
Bi-component polyurethane foaming structural adhesive as well as preparation method and application thereof
CN116622328A